Correlation Between Cyclo-oxygenase-2 and Vascular Endothelial Growth Factor Expression in Canine and Feline Squamous Cell Carcinomas. Issue 4 (May 2016) - Millanta, F.; Andreani, G.; Rocchigiani, G.; Lorenzi, D.; Poli, A.
Summary: Overexpression of cyclo-oxygenase (COX)-2 is involved in tumour growth and spread by modulating the production of angiogenic factors such as vascular endothelial growth factor (VEGF). Expression of COX-2 and VEGF was investigated immunohistochemically in 51 canine and feline cutaneous and non-cutaneous squamous cell carcinomas (SCCs) and the correlation between expression of these molecules and clinicopathological variables was evaluated. COX-2 and VEGF expression was not observed in normal skin keratinocytes. COX-2 overexpression occurred in 53% and 61% of the canine and feline SCCs, respectively. The expression of both markers was higher in cutaneous compared with non-cutaneous SCCs. In both species COX-2 and VEGF expression was correlated with the progression of the disease, but not with the presence of lymphatic invasion, tumour grading or tumour classification in the cutaneous tumours. Further study will be required to understand the role of the COX-2 pathway in angiogenesis in SCC.